Contribution of Sea‐State Dependent Bubbles to Air‐Sea Carbon Dioxide Fluxes. Issue 9 (12th May 2020) - Reichl, B. G.; Deike, L.
Abstract: Breaking surface ocean waves produce bubbles that are important for air‐sea gas exchanges, particularly during high winds. In this study we estimate air‐sea CO2 fluxes globally using a new approach that considers the surface wave contribution to gas fluxes. We estimate that 40% of the net air‐sea CO2 flux is via bubbles, with annual, seasonal, and regional variability. When compared to traditional gas‐flux parameterization methods that consider the wind speed alone, we find high‐frequency (daily to weekly) differences in the predicted gas flux using the sea‐state dependent method at spatial scales related to atmospheric weather (10 to 100 km). Seasonal net differences in the air‐sea CO2 flux due to the sea‐state dependence can exceed 20%, with the largest values associated with North Atlantic and North Pacific winter storms. These results confirm that bubbles are important for global gas‐flux dynamics and that sea‐state dependent parameterizations may improve performance of global coupled models. Key Points: We estimate globally sea‐state dependent carbon dioxide fluxes with a novel gas transfer parameterization Bubbles support approximately 40% of the carbon dioxide uptake by the ocean The bubble contribution and sea‐state dependence is highly variable on regional and seasonal scales